Sistema de Transmissão por Fibra Ótica para uso DidáticoDOI: 10.14209/jcis.1993.3 - Carlos Luna, Juán; Carlos Alvarez, Juán; Vizcaya Guarin, Pedro; Maria Guzmán, Angela; José Kalinowski, Hypolito (Journal of Communication and Information Systems, 2015)
We developed an educational system for fiber optic transmission experiments in undergraduate laboratories of Physics and Engineering. The system has boards for Bit Error Rate measurements, laser and led transmitters, photodetector receivers and noise generator. Due to simplicity of design and use of low cost components it is suitable for the majority of teaching laboratories and helps to consolidate the main concepts of optical communication systems.